Aktivitas Antioksidan dan Antibakteri Ekstrak Etanol Adas Pagar (Eupatorium Capillifolium (Lam.) Small) terhadap Staphylococcus Aureus dan Escherichia Coli - Feblicya Palimbunga; Dwi Aditiyarini; Vinsa Cantya Prakasita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of the study was to investigate the presence of second-order metabolites and the antibacterial and antifungal activities against S. aureus and E. coli in an experimental manner. This study is being conducted using an experimental method. Metabolit is quickly identified by scrining fitokimia. Antioxidant activity was measured using the DPPH method. Antibacterial activity is carried out using the cakram diffusion method. Ekstraksi was carried out by the 96% etanol-maseration process. The results show that the extracted etanol adas pagar contains flavonoid, alkaloid, tanin, saponin, and terpenoid content. Ekstrak etanol adas pagar has strong anti-oxidant activity with an IC50 of 80,56 ppm. Due to its antibacterial potential, ekstrak etanol adas pagar can kill gram-positive Staphylococcus aureus as well as gram-negative Escherichia coli bacteria when applied in concentrations of 100% and 50%, respectively. The main finding of this study is that ekstrak etanol adas pagar can be used as a safe antibacterial and antifungal against the growth of S. aureus and E. coli. Keywords: Adas Pagar, Antibacterial, Antioxidant, Extraction, Metabolite